The Development of PROPOMIMI Learning Techniques With XMIND Assisted For Creative Teacher - Fitriana Eka Chandra (Universitas Islam Jember, 2021)
Abstrack This study aims to describe the process and results of the development of PROPOMIMI learning techniques with XMIND assisted. The type of research used is development research. This research was conducted on tenth grade students at SMKs Al-Akhyar. This research model adopts the 4D Tianggarajan model, but this research was carried out only as 3D. Based on the results of the research that has been carried out, it can be concluded that learning techniques have been successfully developed using a modified 4-D model whose stages include: (1) the Defining Stage which includes the initial and final analysis and subject analysis; (2) Design Phase; and (3) the Development Phase which includes the learning strategy expert test, the learning media expert test and the learning evaluation expert test. The results of the validation percentages provided include 82.1% expert validation of learning strategies, 79% of learning media expert validation and 85.7% of learning evaluation expert validation. Thus, it can be concluded that the PROPOMIMI learning techniques with XMIND assisted is very feasible to use in mathematics learning with an average validation assessment by the validators of 81.3%. Keywords: PROPOMIMI, XMIND, creative